Development of MOSHEE (E-Modul & E-Jobsheet) to Enhance Students' Learning Independence in the Network Measuring Instruments Subject - NOVA RACHMAWATI; Ekohariadi Ekohariadi; Ratna Suhartini; Yessy Yessy; Achmad Imam Agung (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
Learning success is influenced by several factors, one of them is learning media. The shift from teacher-centered learning to student-centered learning requires teachers to act as facilitators in developing media that support learner independence. This study aims to develop MOSHEE (E-module and E-jobsheet) based on Book Creator and to examine its feasibility and effectiveness in improving students’ learning independence in the Network Measurement Tools subject for Grade X TKJ students at SMKN Prigen, Pasuruan. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial was conducted through a quasi-experimental design involving two groups, namely the experimental class and the control class. The results showed that the media validity level reached 93.75%, categorized as highly valid, while the material validity reached 95.07%, categorized as highly feasible. Students’ learning independence reached 90%, indicating that MOSHEE was able to improve students’ learning independence. In addition, a reliability test of the learning independence questionnaire instrument was conducted, resulting in a reliability value of 0.801, which is included in the high category. Based on these findings, MOSHEE is considered feasible as a learning medium and effective in improving students’ learning independence.